Barium Titanate Nanocrystals

By controlling the synthesis of barium titanate nano crystals through specific molar ratios, the collective properties are improved, resulting in high-density aggregates with enhanced dielectric characteristics suitable for advanced electronic devices.

JP7621120B2Active Publication Date: 2025-01-24SAKAI CHEM IND CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021001071
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-06
Publication Date
2025-01-24
Estimated Expiration
2041-01-06

Smart Images

  • Figure 0007621120000003
    Figure 0007621120000003
  • Figure 0007621120000004
    Figure 0007621120000004
  • Figure 0007621120000005
    Figure 0007621120000005
Patent Text Reader

Abstract

To improve the aggregativity of barium titanate nanocrystals.SOLUTION: A barium titanate nanocrystal has a squareness of 0.8 or more. The squareness is obtained by (L×W) / (2×S0), with the absolute maximum length Lnm, diagonal width Wnm and actual area S0 nm2 of the crystal, based on an image of the crystal by transmission electron microscopy. The length Ls of one side of a square in the size corresponding to the actual area S0 nm2 is more than 20 nm to 100 nm or less. The length Ls has a coefficient of variation of 20% or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to barium titanate nanocrystals. [Background technology]

[0002] Barium titanate nanocubes are nanocrystals with a hexahedral shape. Barium titanate nanocrystals can be used as an assembly in which multiple crystal particles are regularly arranged, and it is believed that it is possible to increase the density of the assembly to the theoretical value. The high density of the assembly and local interface distortion brought about by the unique particle shape result in high dielectric properties. It is expected that innovative devices such as high-capacity ferroelectric memories, ultra-high performance dielectric elastomers, and high-performance optical films will be realized by utilizing the self-alignment of nanocrystals and the high dielectric properties of the assembly based on it (for example, Non-Patent Document 1). [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Kazumi Kato, "Development of high-performance small devices using single-crystal nanocubes," ALCA New Technology Briefing (February 24, 2015), presentation material, p. 7 Summary of the Invention [Problem to be solved by the invention]

[0004] As devices become more powerful and functional, there is a demand to improve the aggregation of barium titanate nanocrystals in order to enhance the dielectric properties of the aggregates of barium titanate nanocrystals. However, this is still insufficient. [Means for solving the problem]

[0005] In view of the above, one aspect of the present invention is a barium titanate nanocrystal having a four angle of 0.8 or more, and the four angles are determined by an image of the crystal by a transmission electron microscope, and are expressed as the absolute maximum length L nm, diagonal width W nm, and actual area S0 nm of the crystal. 2 Using the above, the actual area S0 nm is calculated by (L×W) / (2×S0). 2 The present invention relates to a barium titanate nanocrystal, in which the length Ls of one side of a square having a size equivalent to the above is greater than 20 nm and is not more than 100 nm, and the coefficient of variation of the length Ls is not more than 20%. Effect of the Invention

[0006] According to the present invention, the aggregation of barium titanate nanocrystals can be improved. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a diagram showing one side of a barium titanate nanocrystal. [Diagram 2] 1 is a TEM image of an aggregate of BT nanocrystals in Example 2. [Diagram 3] 1 is a TEM image of an aggregate of BT nanocrystals in Example 3. [Figure 4] 1 is a TEM image of an aggregate of BT nanocrystals in Comparative Example 1. [Diagram 5] 1 is a TEM image of an aggregate of BT nanocrystals in Comparative Example 2. [Figure 6] 1 is a TEM image of an aggregate of BT nanocrystals in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Barium titanate nanocrystals] The barium titanate nanocrystals (hereinafter also referred to as BT nanocrystals) according to the embodiment of the present invention have a square angle of 0.8 or more. The square angle is determined by the absolute maximum length L nm, diagonal width W nm, and actual area S0 nm of the crystal, which are determined by a transmission electron microscope image of the crystal. 2Using the above, the actual area S0nm is calculated by (L×W) / (2×S0). 2 The length Ls of one side of a square having a size equivalent to the above is greater than 20 nm and is not more than 100 nm. The coefficient of variation of the length Ls is not more than 20%.

[0009] When the square angle, length Ls, and coefficient of variation of length Ls are within the above ranges, the BT nanocrystals have excellent aggregation properties and can form a high-density aggregate. For example, the porosity of the aggregate can be reduced to 20% or less, and can also be reduced to about 16% or less. The term "BT nanocrystals forming an aggregate" means that multiple BT nanocrystals are regularly arranged based on their self-organizing properties.

[0010] When the length Ls is 20 nm or less, the aggregation of the crystals decreases. When the length Ls is 20 nm or less, the crystal size becomes small, and the ratio of the gaps between the crystals in the aggregate (porosity) becomes large. The above gaps can be formed due to the influence of additives such as organic carboxylic acids used during the synthesis of the crystals that are attached to the crystal surface. Note that the gap here means the area other than the area occupied by the crystals in the aggregate, and the part of the crystal surface where the organic carboxylic acid is attached is considered to be a gap. The smaller the crystal size, the greater the amount of organic carboxylic acid attached per unit mass of the crystal, and the greater the porosity. Note that the above organic carboxylic acid is derived from the material used in the production process of the BT nanocrystals.

[0011] If the length Ls exceeds 100 nm, the dispersibility of the BT nanocrystals in the dispersion medium decreases (the tendency to settle increases) and the self-alignment decreases, which is also disadvantageous in terms of miniaturization of devices.

[0012] If the square angle is less than 0.8, the corners of the BT nanocrystals will be more rounded, the gaps between the crystals will be larger, and the crystals will be less uniform. If the coefficient of variation of the length Ls exceeds 20%, the variation in crystal size increases, and the aggregation of the crystals decreases.

[0013] The length Ls may be 21 nm or more and 100 nm or less, 22 nm or more and 55 nm or less, or 30 nm or more and 55 nm or less. The four angles may be 0.85 or more.

[0014] From the viewpoint of further improving the crystal assembly, the above length L S The coefficient of variation of may be less than 15%, may be 14% or less, or may be 12% or less.

[0015] For example, in the preparation process of the raw material solution described below, by appropriately adjusting the molar ratio of (organic carboxylic acid / Ba ion) and the molar ratio of (hydroxide ion / Ba ion), it is possible to control the square angle, length Ls, and the coefficient of variation of length Ls within the above ranges.

[0016] The above square angle is an index regarding the shape of the BT nanocrystal, and refers to the degree of squareness on the side of the hexahedral BT nanocrystal. The square angle is a maximum of 1, and the more rounded the corners of the BT nanocrystal, the smaller the square angle becomes. When the square angle is 1, it means that the corners of the BT nanocrystal are not rounded and the BT nanocrystal is a neat hexahedron.

[0017] The above length Ls is an index relating to the size of the BT nanocrystal, and corresponds to the length of one side of a square when the side surface of the hexahedral BT nanocrystal is assumed to be square.

[0018] (Measurement of the square angle, length Ls, and coefficient of variation of length Ls of BT nanocrystals) The four angles, length Ls, and coefficient of variation of length Ls of the BT nanocrystals are determined by the following method.

[0019] (i) Preparation of BT nanocrystal aggregates 0.1 g of BT nanocrystals is placed in 10 mL of a non-polar dispersion medium (e.g., toluene) and ultrasonically irradiated for 1 minute using an ultrasonic cleaner (US-106, manufactured by SND Co., Ltd.) to obtain a dispersion of BT nanocrystals. The dispersion of BT nanocrystals is dropped onto the support film of a TEM grid and air-dried to obtain an aggregate (integrated film) of BT nanocrystals.

[0020] (ii) Imaging the aggregates using a transmission electron microscope (TEM) An image of the assembly (integrated film) is obtained using a TEM (JEM-2100F, manufactured by JEOL Ltd.) The magnification of the TEM image is appropriately adjusted so that it contains about 300 to 600 crystal particles.

[0021] (iii) Image processing The TEM image of the aggregate is processed using image analysis software (Mitani Shoji Co., Ltd., WinROOF2015). Specifically, the contrast of the TEM image is appropriately adjusted, and binarization processing is performed to distinguish between areas occupied by crystals and areas other than the areas occupied by crystals. The contrast value is set to, for example, 20 or more. In the binarization processing, processing is performed by specifying the brightness range based on the brightness histogram. The lower limit of the threshold is set to 0, and the upper limit of the threshold may be appropriately set within a range greater than 0 and equal to or less than the peak top of the histogram.

[0022] (iv) Measurement of the four angles (arithmetic mean) of BT nanocrystals Using the TEM image after the above (iii) processing, the "actual area S0", "absolute maximum length L", and "diagonal width W" necessary for calculating the four angles are extracted from the "shape feature" function. Here, the actual area S0 (nm 2) is the area of ​​one side surface 1 of the BT nanocrystal shown in FIG. 1. The absolute maximum length L (nm) is the maximum value of the distance between any two points on the contour of the side surface 1. In FIG. 1, the absolute maximum length L is the distance between two points A1 and A2. The distance between two line segments P1 and P2 that are parallel to the length direction of the absolute maximum length L and sandwich the side surface 1 is the diagonal width W (nm). The direction of the diagonal width W is perpendicular to the direction of the absolute maximum length L. A hypothetical rectangle 2 (a rectangle drawn with dashed lines) is drawn for one side surface 1 of the BT nanocrystal shown in FIG. 1. The hypothetical rectangle 2 is obtained by drawing four line segments that connect the above two points A1 and A2 and the two points B1 and B2 where the above two line segments P1 and P2 touch the side surface 1, as shown in FIG. 1. The corners of the hypothetical rectangle 2 touch the rounded corners of the side surface 1 from the inside. Using the absolute maximum length L and diagonal width W, assume (L × W) / 2 (assumed rectangle 2) area S1 (nm 2 ) If L=W, then hypothetical quadrilateral 2 is a square.

[0023] Using the actual area S0 and the assumed area S1, calculate the four angles using the formula below. Squareness=S1 / S0=(L×W) / (2×S0) For approximately 300 to 600 BT nanocrystals, the four angles are determined by the above method, and the arithmetic average of these angles is calculated.

[0024] (v) Measurement of the length Ls (arithmetic mean) of the BT nanocrystals and its coefficient of variation The length Ls (arithmetic mean) of the BT nanocrystals and its coefficient of variation are calculated by the following method. The actual area S0 (nm 2 ) square root: (S0) 1 / 2 is calculated and the length Ls (nm). The length Ls is calculated for each BT nanocrystal, and the arithmetic mean and coefficient of variation are calculated. The coefficient of variation is the relative standard deviation, which is the value obtained by dividing the standard deviation by the arithmetic mean.

[0025] (Measurement of porosity of aggregates) The porosity of the aggregate of BT nanocrystals is determined by the following method. A TEM image of the BT nanocrystal aggregate is obtained by the same method as for determining the four angles, and an aggregate region where about 100 to 300 BT nanocrystals are regularly arranged is arbitrarily selected, and the TEM image is subjected to the image processing of (iii) above by the same method as for determining the four angles. After image processing, the area Sa enclosed by the outline of the aggregate region and the area Sv occupied by voids within the aggregate region are obtained, and the porosity (%) is calculated as (Sv / Sa) x 100. Note that all areas within the aggregate region other than those occupied by BT nanocrystals are considered to be voids. Sv can be calculated by subtracting the total area of ​​the areas occupied by BT nanocrystals within the aggregate region from Sa.

[0026] [Method of manufacturing barium titanate nanocrystals] A method for producing barium titanate nanocrystals according to one embodiment of the present invention includes a preparation step of obtaining a raw material solution, and a heating step of heating the raw material solution to obtain barium titanate nanocrystals. The raw material solution includes a water-soluble barium salt, a water-soluble titanium complex, an alkali component, an organic carboxylic acid, and water. In the raw material solution, the molar ratio of the organic carboxylic acid to the barium ion is 0.5 or more and 2 or less, and the molar ratio of the hydroxide ion to the barium ion is 1 or more and 2 or less.

[0027] The molar ratio of the organic carboxylic acid to the barium ion is the ratio of the molar amount of the organic carboxylic acid to the molar amount of the Ba ion, and is also referred to as the molar ratio of (organic carboxylic acid / Ba ion) hereinafter. The molar ratio of the hydroxide ion to the barium ion is the ratio of the molar amount of the hydroxide ion to the molar amount of the Ba ion, and is also referred to as the molar ratio of (hydroxide ion / Ba ion) hereinafter. The molar amount of the Ba ion refers to the molar amount of the Ba ion when all of the Ba derived from the water-soluble barium salt exists as an ion in the raw material solution.

[0028] The molar amount of the organic carboxylic acid refers to the molar amount of the organic carboxylic acid added to the raw material solution, and the organic carboxylic acid may or may not be ionized. However, when the organic carboxylic acid contains two or more carboxy groups in one molecule (when the organic carboxylic acid is, for example, a dicarboxylic acid or a carboxylic anhydride (which is a hydrolyzate in the raw material solution)), the molar amount of the organic carboxylic acid is converted into the molar amount of the carboxy groups contained in the organic carboxylic acid.

[0029] The above-mentioned molar amount of hydroxide ions refers to the molar amount of hydroxide ions present in the raw material solution. The hydroxide ions present in the raw material solution refer to the hydroxide ions remaining in the raw material solution after the neutralization reaction of the alkaline component and the acid component contained in the raw material. The molar amount of hydroxide ions can be calculated from the amount of the raw material charged.

[0030] When the molar ratios of (organic carboxylic acid / Ba ion) and (hydroxide ion / Ba ion) are within the above ranges, BT nanocrystals with excellent aggregation properties can be efficiently obtained, and high-density aggregates can be formed.

[0031] When the molar ratio of (hydroxide ion / Ba ion) is within the above range, the amount of seeds generated (the number of crystal grains) decreases, and accordingly, crystal growth is promoted, and the crystal size (particle size) increases exponentially. On the other hand, the variation in crystal size may increase, and the crystal recovery rate may drop sharply. The above phenomenon was not known in the past, and was newly discovered by the present inventors. Based on the above findings, the present inventors further conducted intensive research. As a result, it was newly discovered that when the molar ratio of (hydroxide ion / Ba ion) is within the above range, and the molar ratio of (organic carboxylic acid / Ba ion) is within the above range, the seed generation and crystal growth are arbitrarily controlled, and crystals having a length Ls of more than 20 nm can be stably obtained while reducing the variation in crystal size (while suppressing the coefficient of variation of the length Ls to 20% or less). The present invention is based on the above new findings.

[0032] If the molar ratio of (organic carboxylic acid / Ba ion) is less than 0.5, the square angle of the BT nanocrystals will be low and they will not be able to be arranged regularly.If the molar ratio of (organic carboxylic acid / Ba ion) is more than 2, the viscosity of the raw material solution will increase and the shape of the resulting BT nanocrystals will become non-uniform.

[0033] The smaller the molar ratio of (hydroxide ion / Ba ion), the larger the crystal size (length Ls) tends to be. When the molar ratio of (hydroxide ion / Ba ion) is more than 2, the length Ls may be 20 nm or less. In addition, the coefficient of variation of the length Ls may exceed 20%, and the square angle may be less than 0.8.

[0034] If the molar ratio of (hydroxide ion / Ba ion) is less than 1, the reaction rate decreases, and the BT nanocrystals are not sufficiently obtained, and the aggregates may not be sufficiently formed. Also, the length Ls may exceed 100 nm.

[0035] From the viewpoint of further improving the aggregation of BT nanocrystals, the molar ratio of (hydroxide ion / Ba ion) is preferably 1 or more and less than 1.75, more preferably 1.1 or more and 1.72 or less. In this case, the crystal growth is promoted while the variation in crystal shape is reduced, and it is easy to obtain high-quality BT nanocrystals that can form high-density aggregates. The molar ratio of (hydroxide ion / Ba ion) is more preferably 1.4 or more and 1.72 or less. When the molar ratio of (hydroxide ion / Ba ion) is within the above range, it is possible to efficiently obtain a sufficient amount of BT nanocrystals to form aggregates while increasing the aggregation of the BT nanocrystals. The molar ratio of (hydroxide ion / Ba ion) is particularly preferably 1.64 or more and 1.72 or less. When the molar ratio of (hydroxide ion / Ba ion) is within the above range, it is possible to increase the four angles of the BT nanocrystals and increase the aggregation.

[0036] The hydroxide ion concentration in the raw material solution may be, for example, 0.3 mol / L or more and 0.8 mol / L or less, 0.3 mol / L or more and 0.6 mol / L or less, or 0.4 mol / L or more and 0.6 mol / L or less. The hydroxide ion concentration in the raw material solution refers to a value obtained by dividing the molar amount of hydroxide ions present in the raw material solution by the total amount of water (liters) contained in each raw material (including water) used to prepare the raw material solution.

[0037] [Preparation of raw material solution] In this process, barium ions (Ba 2+ ) and titanium ions (Ti 4+ ) is obtained. In preparing the raw solution, the water-soluble barium salt as the barium source and the water-soluble titanium complex as the titanium source may be added so that the molar ratio of barium to titanium, Ba / Ti, is within the range of 0.95 or more and 1.5 or less (preferably 0.97 or more and 1.2 or less). In the preparation step, the water-soluble barium salt, the water-soluble titanium complex, and water may be added to obtain an aqueous solution containing barium ions and titanium ions, and then an organic carboxylic acid and an alkali component may be added to the aqueous solution. The water-soluble barium salt and the water-soluble titanium complex may be used as an aqueous solution of the barium salt and an aqueous solution of the water-soluble titanium complex, respectively.

[0038] The water-soluble barium salt may be one that dissolves in water in the above preparation step, or one that is difficult to dissolve in water in the above preparation step but dissolves when heated in the above heating step (for example, a barium salt of a higher fatty acid such as barium oleate). Examples of water-soluble barium salts include barium chloride, barium hydroxide, barium salts of fatty acids, and barium nitrate. Among them, the water-soluble barium salt is preferably barium hydroxide. Barium hydroxide does not contain any other elements other than the constituent elements of barium titanate and water. Therefore, when barium hydroxide is used as the barium source, the inclusion of impurities derived from other elements in the synthesis of BT nanocrystals is suppressed, and BT nanocrystals having excellent aggregation properties are easily obtained stably. The water-soluble barium salt may be used alone or in combination of two or more.

[0039] The concentration of Ba ions in the raw material solution may be 0.2 mol / L or more and 2 mol / L or less, or 0.2 mol / L or more and 1 mol / L or less. In this case, it is easy to efficiently obtain high-quality barium titanate nanocrystals. The concentration of Ba ions in the raw material solution refers to a value obtained by dividing the molar amount of Ba ions when all Ba derived from the water-soluble barium salt exists as ions in the raw material solution by the total amount of water (liters) contained in each raw material (including water) used to prepare the raw material solution.

[0040] (Water-soluble titanium complex) The ligand of the water-soluble titanium complex preferably contains a hydroxy acid (salt). Hydroxy acids include, for example, glycolic acid, citric acid, malic acid, tartaric acid, lactic acid, etc. The salt is, for example, an ammonium salt. From the viewpoint of easy availability, the water-soluble titanium complex is preferably a titanium complex containing an ammonium salt of lactic acid as a ligand, and more preferably titanium bis(ammonium lactate) dihydroxide (TALH). The water-soluble titanium complex may be used alone or in combination of two or more kinds.

[0041] (Organic carboxylic acid) The organic carboxylic acid plays a role in controlling the crystal shape. The organic carboxylic acid coordinates to the (100) plane of the barium titanate crystal. This inhibits the crystal growth of the (100) plane and promotes the crystal growth of the (111) plane, making it easier to control the crystal shape to a hexahedron.

[0042] The organic carboxylic acid preferably contains a fatty acid having 6 or more carbon atoms in the main chain. The number of carbon atoms in the main chain of the fatty acid is preferably 10 or more, more preferably 15 or more. The fatty acid may be a saturated fatty acid or an unsaturated fatty acid. Saturated fatty acids having 15 or more carbon atoms in the main chain include, for example, palmitic acid and stearic acid. Unsaturated fatty acids having 15 or more carbon atoms in the main chain include, for example, oleic acid, linoleic acid, linolenic acid, eleostearic acid, and arachidonic acid. From the viewpoint of easiness in obtaining hexahedral nanocrystals, oleic acid is preferable. The organic carboxylic acid may be used alone or in combination of two or more kinds.

[0043] In the raw material solution, the molar ratio of (organic carboxylic acid / Ba ion) may be 0.7 or more and 1.65 or less, or 0.7 or more and 1.5 or less. In this case, the (100) and (111) faces of the barium titanate crystals tend to grow in a well-balanced manner, and the crystal shape is easily controlled to be a hexahedron, which reduces the variation in the crystal shape and is advantageous in reducing the porosity of the aggregate.

[0044] The concentration of the organic carboxylic acid (e.g., oleic acid) in the raw material solution may be, for example, 0.15 mol / L or more and 0.5 mol / L or less. The concentration of the organic carboxylic acid in the raw material solution refers to a value obtained by dividing the molar amount of the organic carboxylic acid added to the raw material solution by the total amount of water (liters) contained in each raw material (including water) used to prepare the raw material solution.

[0045] (Alkaline component) By including an alkaline component in the raw material solution, it is possible to promote crystal growth and reduce the variation in crystal shape. From the viewpoint of cost reduction and environmental load reduction, it is preferable that the alkaline component includes an alkali metal hydroxide. Examples of the alkali metal hydroxide include sodium hydroxide and potassium hydroxide. Among them, the alkali metal hydroxide is preferably sodium hydroxide.

[0046] The concentration of sodium hydroxide in the raw solution may be appropriately adjusted according to the amount of each of the other raw materials added, and is, for example, 0.5 mol / L or more and 1.5 mol / L or less. The concentration of sodium hydroxide in the raw solution refers to the value calculated by dividing the molar amount of sodium hydroxide added to the raw solution by the total amount of water (liters) contained in each of the raw materials (including water) used to prepare the raw solution.

[0047] The alkaline component may contain an amine compound for the purpose of reducing the variation in crystal shape. Examples of the amine compound include primary amine compounds such as tert-butylamine, secondary amine compounds such as dimethylamine, and tertiary amine compounds such as trimethylamine. From the viewpoints that amine compounds are highly ecotoxic and expensive, it is preferable that the alkaline component does not contain an amine compound. By adjusting the concentration of hydroxide ions using an alkali metal hydroxide without using an amine compound, the variation in crystal shape can be reduced.

[0048] [Heating process of raw material solution] In this process, the raw material solution is heated to synthesize barium titanate. That is, BT nanocrystals are obtained. Barium titanate can be obtained by utilizing a hydrothermal reaction, and the raw material solution may be heated while being stirred. From the viewpoint of efficiently obtaining high-quality BT nanocrystals, the heating temperature is preferably 150°C or more and 250°C or less. When the heating temperature is 150°C or more, the synthesis reaction of barium titanate tends to proceed smoothly. When the heating temperature is 250°C or less, the decomposition of the organic carboxylic acid is suppressed, and the effect of controlling the shape of the crystals by the organic carboxylic acid is more reliably obtained. From the viewpoint of sufficiently proceeding the reaction and increasing productivity, the heating time may be, for example, 1 hour or more and 80 hours or less, or 12 hours or more and 48 hours or less.

[0049] [BT nanocrystal cleaning process] Furthermore, after the heating step, a washing step may be performed in which the BT nanocrystals are dispersed in alcohol and washed. Examples of alcohol that can be used include ethanol, methanol, and 2-propanol. In the washing step, the BT nanocrystals obtained in the heating step are separated from water (containing residual components such as organic carboxylic acids dissolved in water).

[0050] The washing step includes, for example, a step (a) of adding alcohol to the reaction solution (water containing BT nanocrystals) after the heating step, followed by centrifugation to obtain a precipitate, and a step (b) of dispersing the precipitate in alcohol, followed by centrifugation to obtain a precipitate. Step (b) may be repeated multiple times. In step (a), it is preferable to thoroughly mix the reaction solution with the alcohol before centrifugation.

[0051] [Classification process of BT nanocrystals] Furthermore, after the heating step, a classification step may be performed in which the BT nanocrystals are dispersed in a non-polar dispersion medium and classified by centrifugation. The classification step is preferably performed after the washing step. Examples of the dispersion method include ultrasonic treatment and stirring with a stirring blade. The non-polar dispersion medium includes a low-polarity organic dispersion medium. As the dispersion medium, a non-polar (low-polarity) aromatic hydrocarbon dispersion medium (e.g., toluene, benzene) or an aliphatic hydrocarbon dispersion medium (e.g., hexane) can be used.

[0052] [Example] Examples of the present invention will be specifically described below, but the present invention is not limited to the following examples.

[0053] Example 1 (Preparation of raw material solution) In a 300 mL polytetrafluoroethylene beaker, 10.1 g of titanium bis(ammonium lactate) dihydroxide (TALH) aqueous solution, 56.1 g of ion-exchanged water, and 5.6 g of barium hydroxide octahydrate, a barium source, were added and stirred for 3 minutes. In this way, an aqueous solution containing TALH, a titanium source, and barium hydroxide, a barium source, was obtained. The TALH aqueous solution was manufactured by Sigma-Aldrich Co., Ltd. (product number 388165, concentration 50 wt%). The barium hydroxide octahydrate was manufactured by Fujifilm Wako Pure Chemical Co., Ltd. (product code 020-00242, special grade reagent).

[0054] While stirring the aqueous solution containing the titanium source and the barium source, 6.5 mL of 7.5 M aqueous sodium hydroxide solution and 4.8 g of oleic acid were added to the aqueous solution in this order and stirred for 5 minutes. The sodium hydroxide used was product code 198-13765 (special grade reagent) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. The oleic acid used was product name PM500 manufactured by Miyoshi Oil Co., Ltd. In this way, the raw material solution was prepared.

[0055] The concentrations of Ba ions and Ti ions in the raw solution were 0.25 mol / L. The Ti ion concentration in the raw solution refers to the value obtained by dividing the molar amount of Ti ions when all Ti derived from the water-soluble titanium complex (TALH) exists as ions in the raw solution by the total amount of water (liters) contained in each raw material (including water) used to prepare the raw solution. The concentration of sodium hydroxide in the raw solution was 0.73 mol / L. The concentration of oleic acid in the raw solution was 0.20 mol / L. The concentration of hydroxide ions in the raw solution was 0.47 mol / L. The molar ratio of (oleic acid / Ba ions) in the raw solution was 0.8. The molar ratio of (hydroxide ions / Ba ions) in the raw solution was 1.88.

[0056] (Heating process of raw material solution) The raw material solution prepared above was transferred to a 100 mL PTFE container (HUT-100, manufactured by San-Ai Scientific Co., Ltd.), sealed in a hot stirrer reaction decomposition apparatus (RDV-TMS-100 aluminum block and HHE-19G-U, manufactured by San-Ai Scientific Co., Ltd.), and heated while stirring. The stirring was performed at a rotation speed of 536 rpm, the heating temperature was 230°C, and the heating time was 24 hours. In this way, barium titanate was synthesized in water. That is, BT nanocrystals were obtained.

[0057] (BT nanocrystal cleaning process) The BT nanocrystals obtained in the heating process were dispersed in ethanol and washed. Specifically, 20 mL of ethanol was added to the reaction solution (water containing BT nanocrystals) after the hydrothermal reaction, and this was transferred to a centrifuge tube. The centrifuge tube was then heated by standing in a warm bath controlled at 50°C to 70°C for 5 minutes, and then the tube was shaken to stir and disperse the reaction solution in the ethanol. The centrifuge tube was placed in a tabletop laboratory centrifuge (Sigma, 3-16L) and centrifuged at a centrifugal acceleration of 2500G for 10 seconds, and the entire supernatant was removed to obtain a precipitate (step (a)).

[0058] Next, 40 mL of ethanol was added to the precipitate in the centrifuge tube, and the mixture was heated and stirred in the same manner as above to disperse the precipitate in ethanol. Then, the mixture was centrifuged in the same manner as above to remove the entire supernatant and obtain a precipitate (step (b)). Step (b) was repeated twice. The precipitate was transferred to a magnetic dish and dried in a thermostatic chamber at 90°C for 6 hours. In this way, BT nanocrystals were obtained.

[0059] The BT nanocrystals obtained above were evaluated as follows. [Evaluation 1: Measurement of the four angles (arithmetic mean), length Ls (arithmetic mean) and coefficient of variation of length Ls] Using the method described above (steps (i) to (v) above), the four angles (arithmetic mean), length Ls (arithmetic mean), and coefficient of variation of length Ls of the BT nanocrystals were determined.

[0060] For the image processing (iii) above, the TEM images of the aggregates were processed using image analysis software (Mitani Shoji Co., Ltd., WinROOF2015) in the following procedure. First, the scale was calibrated. Specifically, the "Manual Calibration" function was used to measure the length of the scale bar written in the analysis condition column of the TEM image, and it was made to correspond to the actual value. Next, all areas except the analysis condition column displayed below the TEM image were selected using a rectangular ROI, and the selected area was cut out to extract the image area related to the crystal particles (aggregate). Next, in order to enhance the contrast of the TEM image, the "Brightness / Contrast" function was used to set the contrast value to 60. Next, median processing was performed to average the brightness. The "Filter" function was used for median processing, and the filter size was set to 9 x 9 pixels. Next, sharpening processing was performed to emphasize the boundary between the crystal particles and the background in the TEM image of the aggregate. The "Edge" function was used for sharpening processing, and the filter size was set to 7 x 7 pixels. Furthermore, binarization processing was performed by specifying the brightness range based on the brightness histogram for the image after the above processing. The lower limit of the threshold was set to 0, and the upper limit of the threshold was set to the peak top of the histogram. After setting the threshold, the areas where the binarization processing was insufficient were slightly corrected using the pen tool.

[0061] [Evaluation 2: Porosity measurement] The porosity of the aggregate of BT nanocrystals was determined by the method described above.

[0062] [Evaluation 3: Measurement of BT reaction rate] 5 g of the BT nanocrystals obtained above was transferred to an alumina crucible, heated in a thermostatic chamber at 130°C for 30 minutes, completely dried, and the mass W1 (g) of the solid content after drying was measured. The dried solid content was then fired at 800°C for 2 hours, and the mass W2 (g) of the solid content after firing was measured. The ratio (percentage) of mass W2 to mass W1, i.e., (W2 / W1) x 100, was calculated as the BT conversion reaction rate (%).

[0063] The barium source becomes barium oleate in the raw material solution, which decomposes during the heating process and reacts with the titanium source. Unreacted barium source remains as barium oleate, and during the above-mentioned firing, the oleic acid derived from the unreacted residual component (barium oleate) decomposes and volatilizes. When there are few unreacted residual components, the amount of volatilization is small, and a high BT conversion reaction rate can be obtained.

[0064] Examples 2 to 5 In the preparation process of the raw material solution, the amounts of sodium hydroxide and oleic acid added were changed to set the concentrations of sodium hydroxide and oleic acid in the raw material solution to the values ​​shown in Table 1. The hydroxide ion concentrations in the raw material solution, and the molar ratios of (oleic acid / Ba ion) and (hydroxide ion / Ba ion) were the values ​​shown in Table 1. Other than the above, BT nanocrystals were produced and evaluated in the same manner as in Example 1.

[0065] Example 6 In the preparation process of the raw material solution, the input amounts of the barium source and titanium source were changed to obtain the barium concentration and titanium concentration in the raw material solution, respectively, as shown in Table 1. The input amounts of sodium hydroxide and oleic acid were changed to obtain the concentrations of sodium hydroxide and oleic acid in the raw material solution, respectively, as shown in Table 1. The hydroxide ion concentration in the raw material solution, and the molar ratios of (oleic acid / Ba ion) and (hydroxide ion / Ba ion) were the values ​​shown in Table 1. Other than the above, BT nanocrystals were produced and evaluated in the same manner as in Example 1.

[0066] [Table 1]

[0067] Comparative Examples 1, 3, and 6 In the preparation process of the raw material solution, barium chloride was used as the barium source. The amounts of sodium hydroxide and oleic acid added were changed to obtain the concentrations of sodium hydroxide and oleic acid in the raw material solution shown in Table 1.

[0068] Tert-butylamine was further added as an amine compound to the aqueous solution containing the titanium source and the barium source. The amount of tert-butylamine added was adjusted so that the concentration of tert-butylamine in the raw solution was 0.48 mol / L. The concentration of the amine compound in the raw solution was calculated by dividing the molar amount of the amine compound added to the raw solution by the total amount of water (liters) contained in each raw material (including water) used in the raw solution.

[0069] The hydroxide ion concentration, (oleic acid / Ba ion) and (hydroxide ion / Ba ion) molar ratios in the raw material solution were the values ​​shown in Table 1. Except for the above, BT nanocrystals were produced in the same manner as in Example 1 and evaluated.

[0070] Comparative Examples 2 and 5 In the preparation process of the raw material solution, the amounts of sodium hydroxide and oleic acid added were changed to set the concentrations of sodium hydroxide and oleic acid in the raw material solution to the values ​​shown in Table 1. The hydroxide ion concentrations in the raw material solution, and the molar ratios of (oleic acid / Ba ion) and (hydroxide ion / Ba ion) were the values ​​shown in Table 1. Other than the above, BT nanocrystals were produced and evaluated in the same manner as in Example 1.

[0071] Comparative Example 4 In the preparation process of the raw solution, barium chloride was used as the barium source. The input amounts of the barium source and titanium source were changed to obtain the barium concentration and titanium concentration in the raw solution shown in Table 1. The input amounts of sodium hydroxide and oleic acid were changed to obtain the sodium hydroxide and oleic acid concentrations in the raw solution shown in Table 1.

[0072] Tert-butylamine was further added as an amine compound to the aqueous solution containing the titanium source and the barium source. The amount of tert-butylamine added was adjusted so that the concentration of tert-butylamine in the raw solution was 0.48 mol / L. The concentration of the amine compound in the raw solution was calculated by dividing the molar amount of the amine compound added to the raw solution by the total amount of water (liters) contained in each raw material (including water) used in the raw solution.

[0073] The hydroxide ion concentration, (oleic acid / Ba ion) and (hydroxide ion / Ba ion) molar ratios in the raw material solution were the values ​​shown in Table 1. Except for the above, BT nanocrystals were produced in the same manner as in Example 1 and evaluated.

[0074] The evaluation results of the BT nanocrystals of Examples 1 to 6 and Comparative Examples 1 to 6 are shown in Table 2.

[0075] [Table 2]

[0076] In Examples 1 to 6, the aggregation of the BT nanocrystals was improved, and the porosity was reduced to 20% or less in all cases. Among them, Examples 2 to 6, in which the (hydroxide ion / Ba ion) molar ratio was 1.1 or more and 1.72 or less, had a lower porosity. The high-density aggregates of Examples 1 to 6 can exhibit excellent dielectric properties when used in ferroelectric memories or dielectric elastomers. As an example, TEM images of the aggregates of BT nanocrystals of Examples 2 to 3 are shown in Figures 2 and 3.

[0077] In Comparative Examples 1 to 3, the molar ratio of (hydroxide ion / Ba ion) was greater than 2, so the porosity increased to 24% or more. In Comparative Example 1, the coefficient of variation of the length Ls was 20% or less, but the length Ls was less than 20 nm, so the gaps between the crystals increased, and the crystal aggregation decreased. In Comparative Example 2, the coefficient of variation of the length Ls was greater than 20%, so the variation in crystal size increased, and the crystal aggregation decreased compared to Comparative Example 1. In Comparative Example 3, the square angle was less than 0.8, so the corners of the hexahedral crystals were more rounded, so the gaps between the crystals increased, and the crystal aggregation decreased compared to Comparative Example 1. TEM images of the aggregates of BT nanocrystals in Comparative Examples 1 to 3 are shown in Figures 4 to 6.

[0078] In Comparative Example 4, where the (hydroxide ion / Ba ion) molar ratio was less than 1, and Comparative Example 6, where the (oleic acid / Ba ion) molar ratio was more than 2, the BT reaction rate was low and sufficient crystals were not obtained, so that aggregates could not be formed. In Comparative Example 5, where the (oleic acid / Ba ion) molar ratio was less than 0.5, the morphology control ability of oleic acid was not exerted, the crystals had low angles, were not regularly arranged, and aggregates could not be formed. [Industrial Applicability]

[0079] The barium titanate nanocrystals according to the present invention are useful for electronic devices such as multilayer capacitors. [Explanation of symbols]

[0080] 1: One side of a BT nanocrystal, 2: Assumed rectangle, L: Absolute maximum length, W: Diagonal width, A1, A2: Two points where the distance on the contour line of the crystal side is maximum, P1, P2: Two line segments that are parallel to the length direction of the absolute maximum length L and sandwich the crystal side, B1, B2: Points where line segments P1, P2 touch the crystal side

Claims

[Claim 1] The barium titanate nanocrystal has a square angle of 0.8 or more; The four angles are the absolute maximum length L nm, diagonal width W nm and actual area S of the crystal, which are obtained from an image of the crystal by a transmission electron microscope. 0 nm 2 Using this, (L × W) / (2 × S 0 ) The actual area S 0 nm 2 The length Ls of one side of a square having a size equivalent to the above is 30 nm or more and 100 nm or less, The variation coefficient of the length Ls is 20% or less.

Citation Information

Patent Citations

  • Method for producing barium titanate nanocrystal

    JP2012188334A

  • Production method of barium titanate coated with highly crystalline silicon dioxide, and barium titanate powder coated with highly crystalline silicon dioxide produced by the method

    JP2015013792A

  • Method for producing strontium titanate fine particles and strontium titanate fine particles

    JP2015151304A

  • Production method of barium titanate particle

    JP2017202942A

  • Nanocrystal film-coated substrate, manufacturing method of same, and manufacuring method of barium zirconate titanate nanocrystal

    US20180247767A1